The University Extension as an Ally in the Early Detection of Breast Cancer - Curcino Santos, Camila; Santos da Cruz, Andreza Priscilla; dos Santos Almeida, Weslaine; Almeida Zaneti, Maria das Graças; de Cássia Rocha Moreira, Rita (Guará Journal, 2019)
This report is the result of an experience of the extension activity which opened the activities of October Pink Campaign in 2017. It was an attempt to stimulate women to do self breast examination and, to promote gynecological examination and mammographic screening in order to detect breast cancer earlier. The early breast cancer detection and a high quality treatment will reduce mortality among women. The breast clinical examination and mammographic screening lead to early diagnosis. Educational actions give support to pathological tracking. In this perspective, teachers and students of Nursing Course in Feira de Santana State University, as well as members of Health Women Extension and Resource Center joined together in an extensionist action to developed strategies to carry out breast examinations in women population in Santo Estevão, a small town in Bahia. The 40 women that integrate the group were between 16 and 75 years old. Among them, 70% had never done a breast clinical examination during their whole life, 67% of them had never done mammographic screening and 15% of them presented breast palpable nodules. In this context, the women welcoming at-tendance represents a way to ensure the inclusion of these women in early diagnosis programs. Besides that, they will develop a conscious ness about breast cancer. In addition, this initiative underlines the social contribution of a public university to this population.